Constructing and disseminating subaltern public discourses in China - Zhang, Weiyu (Javnost (Ljubljana), 2006)
What is the democratic potential of the Internet? Using subaltern public spheres as the theoretical framework, the Internet is expected to empower the subordinated social groups and extend the inclusiveness of democracy. RearWindow to Movies is a Chinese online discussion group, which focuses on the topic of movies. I used this case to answer my research question: How does the online discussion group function as a subaltern public sphere? My research found that the online discussion group supported the concept of subaltern public spheres instead of a unitary public sphere. The online subaltern public sphere provided a safe discursive space for the subaltern public, who was movie fans from the underdeveloped middle class in China. The subaltern public used online spheres to exchange their opinions and critically debated on issues that they were interested in. They successfully constructed their own discourse, which is different from the market discourse and counteracts the domination of the state discourse. In addition, the impactof these discursive practices was disseminated into the offline world by various methods. On the one hand, RearWindow users took use of social resources including those from the commercial forces to show movies that couldnot be reached through the official channels. On the other hand, the interaction with mass media also helped making the subaltern discourses more and more audible. However, both methods have their own limitations, which might harm the subaltern public sphere as well.
Keywords: Kitajska; state; država; democracy; demokracija; javnost; communication; komuniciranje; množične komunikacije; množično komuniciranje; discourse; diskurz; komunikacijska tehnologija; internet; javno mnenje